2017
DOI: 10.1007/s13402-017-0335-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-100 shuttled by mesenchymal stem cell-derived exosomes suppresses in vitro angiogenesis through modulating the mTOR/HIF-1α/VEGF signaling axis in breast cancer cells

Abstract: Overall, our findings suggest that exosomal transfer of miR-100 may be a novel mechanism underlying the paracrine effects of MSC-derived exosomes and may provide a means by which these vesicles can modulate vascular responses within the microenvironment of breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
198
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(205 citation statements)
references
References 66 publications
5
198
0
2
Order By: Relevance
“…They realized that miR‐16 which is enriched in MSC‐derived exosomes, target VEGF and through this way affect endothelial cell proliferation. Similarly, in another study Pakravan et al () have shown that MSC‐derived exosomes decrease the expression of VEGF through modulating mTOR/HIF‐1α signaling pathways in breast cancer. They found that MSC‐derived exosomes contain high levels of miR‐100.…”
Section: Scs‐derived Exosomes and Tumor Angiogenesismentioning
confidence: 80%
“…They realized that miR‐16 which is enriched in MSC‐derived exosomes, target VEGF and through this way affect endothelial cell proliferation. Similarly, in another study Pakravan et al () have shown that MSC‐derived exosomes decrease the expression of VEGF through modulating mTOR/HIF‐1α signaling pathways in breast cancer. They found that MSC‐derived exosomes contain high levels of miR‐100.…”
Section: Scs‐derived Exosomes and Tumor Angiogenesismentioning
confidence: 80%
“…For example, when exosomes were transferred from adriamycin- and docetaxel-tolerant breast cancer-resistant cell lines to the sensitive cell line, some miRNAs (miR-100, miR-222, miR-30a, and miR-17) would generate drug resistance. 17, 2830 In studies on prostatic cancer and docetaxel resistance, the exosomes secreted by drug-resistant cells can regulate the expression of target cell translocators and endow sensitive cells with docetaxel resistance. 31 According to our research, levels of miRNA193 in esophageal cancer drug-resistant cell line TE-1/DDP and exosome TE-1/DDP/exo significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miRNA was normalized to U6 small nuclear RNA (U6snRNA). The fold changes of gene expression were determined using the 2 −ΔΔCt method (Hayat Nosaeid et al, ; Pakravan et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Down-regulation of the lncRNA H19 and miR-675 during neural differentiation of BMSCs of miRNA was normalized to U6 small nuclear RNA (U6snRNA). The fold changes of gene expression were determined using the 2 ÀDDCt method (Hayat Nosaeid et al, 2009;Pakravan et al, 2017). NSE and MAP-2 proteins were detected by immunocytochemistry (ICC) according to the standard protocol.…”
Section: Quantitative Real-time Pcr and Immunocytochemistrymentioning
confidence: 99%